Phase I metabolism of 3-methylindole, an environmental pollutant, by hepatic microsomes from carp (Cyprinus carpio) and rainbow trout (Oncorhynchus mykiss) - Zlabek, Vladimir; Burkina, Viktoriia; Borrisser-Pairó, Francesc; Sakalli, Sidika; Zamaratskaia, Galia (Chemosphere, 2016)
We studied the in vitro metabolism of 3-methylindole (3MI) in hepatic microsomes from fish. Hepatic microsomes from juvenile and adult carp (Cyprinus carpio) and rainbow trout (Oncorhynchus mykiss) were included in the study. Incubation of 3MI with hepatic microsomes revealed the time-dependent formation of two major metabolites, 3-methyloxindole (3MOI) and indole-3-carbinol (I3C). The rate of 3MOI production was similar in both species at both ages. No differences in kinetic parameters were observed (p = 0.799 for Vmax, and p = 0.809 for Km). Production of I3C was detected only in the microsomes from rainbow trout. Km values were similar in juvenile and adult fish (p = 0.957); Vmax was higher in juvenile rainbow trout compared with adults (p = 0.044). In rainbow trout and carp, ellipticine reduced formation of 3MOI up to 53.2% and 81.9% and ketoconazole up to 65.8% and 91.3%, respectively. The formation of I3C was reduced by 53.7% and 51.5% in the presence of the inhibitors ellipticine and ketoconazole, respectively. These findings suggest that the CYP450 isoforms CYP1A and CYP3A are at least partly responsible for 3MI metabolism. In summary, 3MI is metabolised in fish liver to 3MOI and I3C by CYP450, and formation of these metabolites might be species-dependent.
Keywords: Metabolic Detoxication, Phase I; játra; jaterní mikrozomy; Oncorhynchus mykiss; indoly; Microsomes, Liver; techniky in vitro; druhová specificita; Indoles; kapři; elipticiny; 3-methylindole; Cytochrome P450; Oxindoles; zvířata; Cytochrome P-450 Enzyme Inhibitors; Ketoconazole; ketokonazol; Skatole; Carps; Cytochrome P-450 Enzyme System; skatol; Liver; I. fáze biotransformace; Indole-3-carbinol; Hepatic microsomes; oxindoly; Species Specificity; Water Pollutants, Chemical; In Vitro Techniques; Animals; Ellipticines; 3-hydroxy-3-metyloxindole; inhibitory cytochromu P450; systém (enzymů) cytochromů P-450; chemické látky znečišťující vodu